Evaluate effectiveness of a traffic light control approach based on simulation - Zhang, Yi Ming (2015)
This project aims to use VISSIM to model a traffic network, apply a new developed traffic control approach and evaluate its effectiveness under different traffic situations such as off-peak hours, peak hours, and traffic under accidents. The whole project is divided into three parts. In the first part, the developed traffic control approach will be introduced. In the third part, the functions of VISSIM and the simulation of the traffic control approach will be shown and analyzed. At last, the author will make a conclusion about the traffic control approach and the simulation through VISSIM.